Treatment with Evasin‐3 abrogates neutrophil‐mediated inflammation in mouse acute pancreatitis. (October 2014) - Montecucco, Fabrizio; Mach, François; Lenglet, Sébastien; Vonlaufen, Alain; Gomes Quinderé, Ana Luíza; Pelli, Graziano; Burger, Fabienne; Galan, Katia; Dallegri, Franco; Carbone, Federico; Proudfoot, Amanda E.; Vuilleumier, Nicolas; et al.
Abstract Background Acute pancreatitis is characterized by inflammatory processes affecting not only the pancreas, but also the lung. Here, we investigated timing of leucocyte infiltration and chemokine expression within lung and pancreas during pancreatitis and whether treatments selectively inhibiting chemokines (using Evasins) could improve organ injury. Material and methods C57Bl/6 mice were submitted in vivo to 10‐h intraperitoneal injections of cerulein and followed for up to 168 h. Five minutes after the first cerulein injection, a single intraperitoneal injection of 10 μg Evasin‐3, 1 μg Evasin‐4 or an equal volume of vehicle (PBS) was performed. Leucocytes, reactive oxygen species (ROS), necrosis and chemokine/cytokine mRNA expression were assessed in different organs by immunohistology and real‐time RT‐PCR, respectively. Results In the lung, neutrophil infiltration and macrophage infiltration peaked at 12 h and were accompanied by increased CXCL2 mRNA expression. CCL2, CXCL1 and TNF‐alpha significantly increased after 24 h as compared to baseline. No increase in CCL3 and CCL5 was observed. In the pancreas, neutrophil infiltration peaked at 6 h, while macrophages increased only after 72 h. Treatment with Evasin‐3 decreased neutrophil infiltration, ROS production and apoptosis in the lung and reduced neutrophils, macrophages apoptosis and necrosis in the pancreas. Evasin‐4 only reduced macrophage content in the lung and did not provide any benefit at the pancreas level. Conclusion Chemokine production and leucocyte infiltration are timely regulated in lung and pancreas during pancreatitis. CXC chemokine inhibition with Evasin‐3 improved neutrophil inflammation and injury, potentially interfering with damages in acute pancreatitis and related pulmonary complications.